2019
DOI: 10.1016/j.heliyon.2019.e02867
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal attachment in mental health and dyadic relationships in war trauma

Abstract: Background: Infant care is a demanding task in dangerous war conditions, but research on the wellbeing of mother-infant dyads is mainly available in peaceful conditions. Knowledge on protective versus risking processes is especially vital for tailoring effective help, and the present study proposes the maternal attachment style to play an important role in dangerous war conditions. Objective: The study analyses, first, how various traumatic war events, such as losses, horrors and life-threat, are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…Studying mothers and infants between the ages of 6 and 18 months, Qouta et al (2021) echoed these findings on the importance of good mental health during pregnancy (even under such wartime conditions) to be associated with more optimal EA-SR. Using the same sample which follows mothers from pregnancy to 18 months of infant age, Punamäki et al (2019) investigated the effect of mother's self-reported attachment style at 17-18 months under wartime conditions, reporting that an avoidant attachment was negatively related to self-reported EA-SR at 6-7 and 17-18 months. Potentially surprising is that a self-reported secure attachment actually did not serve a protective role in relation to EA-SR.…”
Section: Resultsmentioning
confidence: 99%
“…Studying mothers and infants between the ages of 6 and 18 months, Qouta et al (2021) echoed these findings on the importance of good mental health during pregnancy (even under such wartime conditions) to be associated with more optimal EA-SR. Using the same sample which follows mothers from pregnancy to 18 months of infant age, Punamäki et al (2019) investigated the effect of mother's self-reported attachment style at 17-18 months under wartime conditions, reporting that an avoidant attachment was negatively related to self-reported EA-SR at 6-7 and 17-18 months. Potentially surprising is that a self-reported secure attachment actually did not serve a protective role in relation to EA-SR.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a longitudinal study by Easterbrooks et al [31] showed a relationship between EA and a child's insecure attachment measured at 12-18 months and 7-8 years old. Other studies have revealed the differential associations between EA and maternal attachment styles (see [32]).…”
Section: Emotional Availability and Attachmentmentioning
confidence: 93%
“…2017; Исакова 2020; Суворова и др. 2016; Cooke et al 2019;Punamäki et al 2019]. Эти взаимоотношения также могут быть предиктором травматизации личности.…”
Section: Introductionunclassified